Developing cultural humility through critical service learning - Breda, Karen Lucas; Groot, Kim; Towle, Antoinette (Ciencia y enfermería, 2013)
Marked inequities or disparities in health care and health outcomes exist for millions in the United States of America. Urban apartheid and increasing social stratification separate social groups making it difficult for them to understand each other. Many U.S. health care professionals, including nurses, hold negative stereotypes toward the urban poor and disenfranchised. Creating vehicles for understanding and respect between health care professionals and the social groups they care for is needed. Cultural humility uses self-reflection, self-critique, openness and transcendence to address power inequities between providers and clients. "Critical service-learning" is a type of "service-learning" that adopts the tenets of critical theory and pedagogy in engaged partnerships to foster social responsibility and a justice-oriented framework. The purpose of this article is to showcase Project Horizon, an innovative university-based health and social advocacy partnership that uses critical service learning with the urban community to foster cultural humility. Project Horizon outcomes show that this long-term engaged partnership is an effective vehicle for developing and enhancing cultural humility among health care professionals participating in the endeavor. Implications: Replication of social and health advocacy projects such as the one conducted through Project Horizon can be made in other settings to increase the capacity for democratically oriented nurses and other health care professionals who have an enhanced sense of cultural humility.
Keywords: Critical service learning; Cultural humility; Health consortia; Health personnel; Healthcare disparities; dept.wll